Factors Influencing Consumers’ Purchase Intentions towards Private Label Products - Sharma, Bhanu Bhakta; Adhikari , Muna (Shiksha Shastra Saurabh, 2025)
Retailers and store owners are starting to introduce their own distinctive items under their own brand names, which has led to a rise in the popularity of private label brands (PLBs). Formerly restricted to being sold by specific retail chains, private label businesses have grown to provide a wide variety of goods. The main aim of this study is to identify the factors and variables that have had a substantial impact on the consumers' decision to purchase private label brands. The quantitative research approach was followed, and data were collected by an organized questionnaire survey. Three hundred and ninety-nine responses, utilizing the connivance sampling technique, were gathered from the target respondents was consumers from supermarkets, and resellers. The findings of the study have demonstrated that the purchasing habits of consumers are significantly impacted by Perceived Price, Packaging, and Perceived Risk, which have a substantial impact on Purchase Intention towards Private Label Products. However, Perceived Quality has had no significant effect on Purchase Intention. It is suggested that retailers should effectively manage pricing, packaging, and risk perceptions in order to enhance consumer assurance and improve the consumption of private label products.The study serves as a guide for further research in this area and offers scholars useful insights particularly in Nepal where there is a lack of literature on private label products.